Chlorination of oxybenzone: Kinetics, transformation, disinfection byproducts formation, and genotoxicity changes. (July 2016) - Zhang, Shujuan; Wang, Xiaomao; Yang, Hongwei; Xie, Yuefeng F.
Abstract: UV filters are a kind of emerging contaminant, and their transformation behavior in water treatment processes has aroused great concern. In particular, toxic products might be produced during reaction with disinfectants during the disinfection process. As one of the most widely used UV filters, oxybenzone has received significant attention, because its transformation and toxicity changes during chlorine oxidation are a concern. In our study, the reaction between oxybenzone and chlorine followed pseudo-first-order and second-order kinetics. Three transformation products were detected by LC-MS/MS, and the stability of products followed the order of tri-chloro-methoxyphenoyl > di-chlorinated oxybenzone > mono-chlorinated oxybenzone. Disinfection byproducts (DBPs) including chloroform, trichloroacetic acid, dichloroacetic acid and chloral hydrate were quickly formed, and increased at a slower rate until their concentrations remained constant. The maximum DBP/oxybenzone molar yields for the four compounds were 12.02%, 6.28%, 0.90% and 0.23%, respectively. SOS/umu genotoxicity test indicated that genotoxicity was highly elevated after chlorination, and genotoxicity showed a significantly positive correlation with the response of tri-chloro-methoxyphenoyl. Our results indicated that more genotoxic transformation products were produced in spite of the elimination of oxybenzone, posing potential threats to drinking water safety. This study shed light on the formation of DBPs and toxicity changes during the chlorination process of oxybenzone. Graphical abstract: Highlights: Oxybenzone reacted quickly with chlorine. Transformation product 2, 4, 6-trichloro-3-methoxyphenol was comparably stable. High amounts of chloroform and TCAA were formed during chlorination of oxybenzone. Significantly elevated genotoxicity was observed after chlorination of BP-3.